Contribution of India's Job Creation Sectors: A Comparative Study of Organized and Unorganized Sectors - Sreedhar, Shalini; Kadel, Lakhan Bhaskar (Journal of Research in Science and Engineering, 2025)
India has experienced rapid economic growth, structural shift in the economy, increase in educational attainment levels and rapid urbanization in the last 25 years. In the context of this rapid economic growth changes have also been occurred in the labour market of India. New jobs are created, competition takes place, and consumer’s choice has increased with the increase in economic efficiencies and all factors in turn leads to further economic growth. Labour market of India is divided in to two sectors viz; organised and unorganised sectors. Changes in the economy also bring changes in the employment in these two sectors in different states. Again, both the sectors have a significant contribution towards the national economy, growth in the economy also bring changes in their respective share towards the economy of the country. In this paper an attempt has been done to make a comparative analysis of states with regard to employment. Special emphasis is also given on industry wise employment differences in these two sectors. Contribution of these sectors towards country’s economy is also analyzed here. (Organised Sector, Unorganised Sector, Employment, States of India, Net Domestic Product.)